Projekt Infrastruktura Niepodległości – międzywojenny powiat kaliski - Rabiega, Mateusz (Lodz University of Technology. Press, 2020)
Actions taken as a part of the Infrastructure of Independence project concerning the interwar Kalisz county resulted in the creation of an exhibition and a brochure about the architectural heritage of the region and modernization processes which took place there in the interwar period.

Działania podjęte w ramach części projektu Infrastruktura Niepodległości dotyczącej międzywojennego powiatu kaliskiego zaowocowały powstaniem wystawy i broszury opowiadających o dziedzictwie architektonicznym regionu i procesach modernizacyjnych w nim zachodzących w dwudziestoleciu międzywojennym.
Infrastructure of Independence project – the interwar Kalisz county
eng.abstract
Keywords: Kalisz; dwudziestolecie międzywojenne; odbudowa; wystawa; interwar period; rebuilding; exhibition